100 things to know about saving the planet - Hall, Rose; Martin, Jerome (Writer of children's books); James, Alice (Editor); Stobbart, Darran; Frith, Alex (Children's author); Mumbray, Tom; Reynolds, Eddie; Cook, Lan; Oldham, Matthew; Polo, Parko; Byron, Dominique; Murray, Dale Edwin; et al. (2020)
How could plastic-eating bacteria help reduce waste? Can a river be given human rights? Could we generate all the power we need from the sun and the wind? How do woolly sweaters help penguins in peril? Would building a giant sunshade in space stop the world from overheating? Find the answers to these questions and more in this bold, graphic and exciting book, full of big, small and unexpected ways to save the planet.
S
Includes index.
b
b
Keywords: Environmental protection -- Juvenile literature; Environmental responsibility -- Juvenile literature; Environmental protection -- Miscellanea -- Juvenile literature; Environmental protection; Environmental responsibility; Juvenile works